High speed multi-channel data acquisition technique for efficient hardware utilization using quad data rate approach - Chauhan, Priyanka; Israni, Dippal; Jasani, Karan; Makwana, Ashwin (International Journal of Engineering and Technology, 2018)
Data acquisition is the most demanding application for the acquisition and monitoring of various sensor signals. The data received are processed in real-time environment. This paper proposes a novel Data Acquisition (DAQ) technique for better resource utilization with less power consumption. Present work has designed and compared advanced Quad Data Rate (QDR) technique with traditional Dual Data Rate (DDR) technique in terms of resource utilization and power consumption of Field Programmable Gate Array (FPGA) hardware. Xilinx ISE is used to verify results of FPGA resource utilization by QDR with state of the art DDR approach. The paper ratiocinates that QDR technique outperforms traditional DDR technique in terms of FPGA resource utilization.Â Â